Pengaruh Pemberian Ampas Tahu Fermentasi Sebagai Pakan Konvensonal Terhadap Biaya Produksi Itik Pedaging - Agus Hadi Prayitno; Budi Prasetyo; Anang Sutirtoadi; Ahmad Sa'Roni (Jurnal Ilmu Peternakan Terapan, 2019)
This study was conducted to determine the effect of fermented tofu waste (ATF) as conventional feed on the cost of broiler duck production. 200 day old ducks (DOD) were maintained. The experimental design used a completely randomized design (CRD) consisting of 4 feed treatments. Each treatment consisted of 5 replications. Each replication consisted of 10 DOD. The research treatments were: P0 (100% BR1), P1 (90% BR1 and 10% ATF), P2 (80% BR1 and 20% ATF), and P3 (70% BR1 and 30% ATF). The parameters were production costs, income, and income over feed costs. The results were analyzed using analysis of variance (ANOVA). Different results continued using the Least Significant Difference test (LSD 1% and 5%). Giving ATF to level 30% in feed had an effect (P <0.05) on feed costs and was highly significant (P <0.01) on income over feed costs, but does not affect income. Giving ATF in feed up to level 30% as conventional feed can reduce production costs in maintaining of ducks.Â